1986
DOI: 10.1002/elps.1150070506
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis on uncrosslinked polyacrylamide: Molecular sieving and its potential applications

Abstract: Uncrosslinked polyacrylamide, a viscous liquid, provides a molecular sieving effect in electrophoresis qualitatively the same as that of crosslinked gels. This finding confirms previous results by others using uncrosslinked polyacrylamide mixed with various gel matrices. It provides a sieving medium constituted by an entirely and necessarily random association of inert fibers, as stipulated for interpretation of migration by the Ogston theory. Ferguson plots of several proteins in uncrosslinked polyacrylamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The results in this paper clearly show t4at in PEO-mediated capillary electrophoresis of SDS-protein complexes, increasing the concentration of the same chain length polymer solution or increasing the chain length of similar concentration, or both, increases the sieving capability of the polymer solution. Tietz and Chrambach [43] suggested that the average apparent chain length of a crosslinked polymer is always longer than the similar molecular mass non-crosslinked polymer. Therefore, some crosslinking (either chemical or dynamic) should increase the separation capability of a given polymer network.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this paper clearly show t4at in PEO-mediated capillary electrophoresis of SDS-protein complexes, increasing the concentration of the same chain length polymer solution or increasing the chain length of similar concentration, or both, increases the sieving capability of the polymer solution. Tietz and Chrambach [43] suggested that the average apparent chain length of a crosslinked polymer is always longer than the similar molecular mass non-crosslinked polymer. Therefore, some crosslinking (either chemical or dynamic) should increase the separation capability of a given polymer network.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the important operational variables in gel electrophoresis based analysis of DNA fragments, such as sieving matrix concentration, applied electric field strength, separation temperature, etc., have been well characterized in conventional slab-gel electrophoresis [16,17], capillary gel electrophoresis (CGE) [18,19] and ultrathinlayer gel electrophoresis (UTLGE) [20,21]. Yet, the migration properties of dsDNA molecules are somewhat different in these various separation formats.…”
Section: Introductionmentioning
confidence: 99%
“…Linear polymers, such as noncross-linked polyacrylamide [2], derivatized celluloses [3], polyethylene oxides [4] and polyvinylpyrrolidone (PVP) [5] have all been demonstrated to be effective in electric field mediated size separation of DNA molecules. Although, the advantages of these noncross-linked polymers have been demonstrated almost entirely in capillary electrophoresis applications [6], it had been shown that very high concentration linear polymers can also be used in planar separation format [7,8]. This lower viscosity noncross-linked polymers are easily replaced within capillary columns [9] supporting repetitive work with these matrices.…”
Section: Introductionmentioning
confidence: 99%